Comparison between HSV-1 Ag Detection Techniques by ELISA and Real-Time PCR in Breast Cancer Patients Suffering from Periodontitis - Jasim, Saif S.; Taha, Ghada I. (Journal of the Faculty of Medicine Baghdad, 2023)
Background: Periodontitis is a long-standing infection that destroys the gums, periodontal ligaments, and the alveolar bone that supports the teeth. Inflammation of the gums and chronic periodontitis are both caused by the bacteria in the dental plaque and the herpes viruses, especially types 1 and 2 of the herpes simplex virus.Objectives: To compare the ELISA and real-time PCR as ways to detect the herpes simplex virus in breast cancer patients with periodontitis who are receiving chemotherapy. Cases and methods: In this case-control study, a total of 90 subjects (30 with periodontitis with breast cancer after receiving chemotherapy, 30 with periodontitis (without chemotherapy treatment), and 30 cases who do not have periodontitis (healthy gingiva) and without breast cancer as a healthy control group. The mean±SD age was (51.06±8.521). Enzyme-linked immunosorbent assay (ELISA) kits were used for the analysis and Real-Time PCR to detection of Herpes simplex virus-1 in saliva samples.Results: In the present study, the incidence of HSV-1 Ag in patients having periodontitis and receiving chemotherapy was high but not significantly so, compared with those having periodontitis but without chemotherapy and the healthy control group. In contrast, the result of Real-time PCR was positive (13.3%) and (10.0%) which proves the presence of HSV in most patients with periodontitis without chemotherapy and with periodontitis receiving chemotherapy but was not significant (p>0.05).Conclusion: Real-time PCR was able to back up ELISA's findings in this study. Since ELISA is more cost-effective than real-time PCR, it is advised that the first screening may be performed using ELISA, and then positive samples might be investigated with real-time PCR to confirm the presence of HSV-DNA.